Unravelling potential biomarkers for acute and chronic brucellosis through proteomic and bioinformatic approaches - Yang, Yuejie; Qiao, Kunyan; Yu, Youren; Zong, Yanmei; Liu, Chang; Li, Ying (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction This study aimed to identify biomarkers for acute and chronic brucellosis using advanced proteomic and bioinformatic methods. Methods Blood samples from individuals with acute brucellosis, chronic brucellosis, and healthy controls were analyzed. Proteomic techniques and differential expression analysis were used to identify differentially expressed proteins. Co-expression modules associated with brucellosis traits were identified using weighted gene co-expression network analysis (WGCNA). Results 763 differentially expressed proteins were identified, and two co-expression modules were found to be significantly associated with brucellosis traits. 25 proteins were differentially expressed in all three comparisons, and 20 hub proteins were identified. Nine proteins were found to be both differentially expressed and hub proteins, indicating their potential significance. A random forest model based on these nine proteins showed good classification performance. Discussion The identified proteins are involved in processes such as inflammation, coagulation, extracellular matrix regulation, and immune response. They provide insights into potential therapeutic targets and diagnostic biomarkers for brucellosis. This study improves our understanding of brucellosis at the molecular level and paves the way for further research in targeted therapies and diagnostics.